The dysfunction in intestinal microorganisms and enzyme activity as significant contributors to diarrhea with kidney-yang deficiency syndrome - Zhou, Mengsi; Li, Xiaoya; Wang, Xuehong; Deng, Na; Cai, Ying; Tan, Zhoujin (Frontiers in Microbiology, 2024)
Object To investigate the pathogenesis of diarrhea with kidney-yang deficiency syndrome by examining characteristic changes in intestinal microorganisms, enzyme activities, oxidative stress, and metabolism indices. Methods Twenty mice were randomly and equally divided into control group (NC) and model group (NM). Mice in NM group received adenine suspension at a dosage of 50 mg/(kg⋅day) by gavage, 0.4 mL/time, once a day for 14 days, and Folium sennae decoction at a dosage of 10 g/(kg⋅day) by gavage, 0.4 mL/time, once a day for 7 days, starting on 8th day. Mice in NC group were administered an equivalent amount of sterile water by gavage once a day for 7 days, and twice a day from the 8th day. After modeling, assessments encompassed microbial culture, organ index calculation, microbial and enzyme activity detection, malondialdehyde (MDA) content determination, superoxide dismutase (SOD) activity, blood biochemical tests, and observation of kidney tissue pathological changes. Results The results showed that in NM group, a reduction in the number of Lactobacillus and Bifidobacteria was noted, accompanied by an increase in the number of bacteria and E. coli. Xylanase activity in the intestinal contents and mucosa, protease activity in the intestinal mucosa, and intestinal mucosa microbial activity were diminished. Conversely, the activities of amylase, sucrase, and lactase increased in intestinal mucosa. Additionally, there was an elevation in the level of MDA. Renal tubular dilatation and inflammatory cell infiltration were observed in the renal interstitium. Conclusion These dysfunctions in intestinal microorganisms and enzyme activities suggest potential involvement in diarrhea with kidney-yang deficiency syndrome.